COMPARATIVE STUDY OF TRADITIONAL AND INTERACTIVE HEALTH EDUCATION MODELS ON COMMUNITY BEHAVIOR CHANGES - Sidabutar, Sondang; Harahap, Veryyon; Ermafina, Pratiwi (Jurnal Ilmiah METADATA, 2023)
This study comparatively analyzed the impact of traditional versus interactive health education models on community behavioral change, guided by Social Cognitive Theory and the Health Belief Model. Utilizing a quasi-experimental design with 200 participants randomly assigned to either a lecture-based traditional group or a discussion-based interactive group, the research assessed behavioral changes in healthy eating and physical activity through validated questionnaires and observational checklists. Results indicated that the interactive model led to significantly greater and more sustained behavioral improvements (p < 0.001, Cohen's d = 1.25), evidenced by higher self-efficacy and adoption rates at a three-month follow-up. These findings suggest that interactive approaches are superior for promoting positive and lasting health behaviors, offering practical implications for public health education strategies and contributing empirically to constructivist learning theories in health promotion.